Spontaneous Multifocal Endometriosis: Ovarian and Umbilical Involvement Without Prior Surgery - Prilly Astari; Ong Tjandra; Airine Stefanie Lians (Tirtayasa Medical Journal, 2026)
Umbilical endometriosis is a rare manifestation of extra-pelvic endometriosis and is frequently underdiagnosed, particularly in women without prior abdominal surgery or infertility. Its clinical presentation may mimic other umbilical pathologies, leading to delayed recognition. A 34-year-old multiparous woman presented with a 3-month history of cyclical bleeding from the umbilicus associated with a painful umbilical nodule, severe dysmenorrhea, deep dyspareunia, and right-sided pelvic pain. She had no history of abdominal or pelvic surgery. Physical examination revealed a firm, reddish umbilical nodule with active bleeding. Ultrasonography demonstrated a large right ovarian endometrioma with a ground-glass appearance. The patient underwent laparotomy with right salpingo-oophorectomy and complete excision of the umbilical lesion. Histopathological examination confirmed endometriosis in both sites. Complete symptom resolution was observed at two-week follow-up. This case highlights spontaneous multifocal endometriosis involving the ovary and umbilicus in a non-infertile, multiparous woman, emphasizing the need for heightened clinical suspicion. Limited access to advanced imaging such as MRI did not preclude accurate diagnosis when clinical, ultrasonographic, and pathological findings were integrated. Umbilical endometriosis should be considered in patients with cyclical umbilical symptoms regardless of parity or fertility status. Early recognition and surgical management are crucial to prevent misdiagnosis and prolonged morbidity.